PEMASANGAN LAMPU PENERANGAN JALAN UMUM (PJU) DENGAN SISTEM PANEL SURYA DI KELURAHAN JENEBORA - Misrianto, Misrianto; Junaidi, Bagus (LPPM Uncen, 2024)
Lighting is one of the basic needs of today's society. The purpose of PkM is to identify, design, and implement the installation of public street lighting with the main objective of improving the safety and welfare of the community in doing activities at night. The problem of this PkM is the lack of lighting in the RT 09 area of Jenebora Village. This PkM method is carried out by observing the PkM location in RT 09 which is located in Jenebora Village to discuss with RT 09 residents and carry out the installation of public street lighting lamps through initial observations, activity implementation, and evaluation. The number of samples was 5 people with a population of 40 residents of RT 09, and used data processing methods with 2 approaches. First, using a pretest before treatment. This treatment aims to determine the knowledge of the object of PkM with this activity, it is hoped that motorists and pedestrians will be helped by the installation of street lighting. At this stage, treatment is carried out by providing assistance to residents of RT 09 about the importance of installing these lighting lamps. After treatment, the sample was given a pretest to determine the changes after treatment. The results of the PkM show that the residents of RT 09 are greatly helped by the installation of these street lighting lamps and the conclusion is that there is a difference between the installation of street lighting and the installation of street lighting.